Recalibrating Parate Executie, Navigating Legal Pluralism, Criminalization Risks and Procedural Governance In Indonesian Fiduciary - Chandra Erick Manaek Pandapotan Lumban Gaol; Lastuti Abubakar; Roni Heilig Marpaung (Journal of Law and Policy Transformation, 2025)
The landscape of fiduciary execution (jaminan fidusia) in Indonesia has been fundamentally reshaped by Constitutional Court Decisions No. 18/PUU-XVII/2019 and No. 2/PUU-XIX/2021. These landmark rulings, while aiming to bolster debtor protection under the 1945 Constitution, have curtailed the creditor's right of direct execution (parate executie) as originally established by Law No. 42 of 1999. This judicial intervention has engendered a state of profound legal ambiguity, creating a perilous enforcement vacuum where the lines between lawful execution and criminal conduct have become dangerously blurred. This article employs a normative legal research methodology, incorporating doctrinal, statutory, case, and comparative approaches to analyze this complex legal problematic. We argue that the Court's decisions, by introducing the vague and procedurally undefined prerequisites of a post-default "agreement on default" and "voluntary surrender," have inadvertently amplified the risks of criminalization for all parties—creditors, debtors, and assisting law enforcement. The research finds that in the absence of clear legislative amendment or binding Supreme Court guidance, the existing legal framework is inadequate to ensure both economic efficiency and procedural justice. As a novel contribution, this paper posits that principles derived from international governance and risk management standards, specifically the ISO/IEC family (e.g., ISO 9001, ISO 31000, ISO 37301), can serve as a crucial non-legislative framework for creditors to develop robust, transparent, and defensible execution protocols. Such a system of private governance can mitigate criminalization risks, demonstrate good faith, and restore a measure of legal certainty, thereby providing a vital bridge over the troubled waters of Indonesia's current fiduciary enforcement regime.